Sectarian conflict in Saudi Arabia, "Shiite question" - A. V. Fedorchenko (Vestnik MGIMO-Universiteta, 2013)
The article deals with the the problems of Shiites community in Saudi Arabia. To this end, issues such as the position of the Shiites in the KSA, the problem of their participation in the public life of the kingdom, the growing protest movement in this community are analyzed. The author assess the prospects for the settlement of inter-confessional conflict between Sunnis and Shiites in the kingdom.